Profiling of a wide range of neurochemicals in human urine by very-high-performance liquid chromatography-tandem mass spectrometry combined with in situ selective derivatization - Lee, Wonwoong; Park, Na Hyun; Ahn, Tae-Beom; Chung, Bong Chul; Hong, Jongki (ELSEVIER SCIENCE BV, 2017)
Development of a reliable analytical method of neurochemicals in biological fluids is important to discover potential biomarkers for the diagnosis, treatment and prognosis of neurological disorders. However, neurochemical profiling of biological samples is challenging because of highly different polarities between basic and acidic neurochemicals, low physiological levels, and high matrix interference in biological samples. In this study, an ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method combined with in situ selective derivatization for comprehensive profiling of 20 neurochemicals in urine was developed for a wide range of neurochemicals. In situ selective derivatization greatly improved the peak capacity on a reversed-phase C18 column and sensitive mass detection in LC-ESI-MS/MS-positive ion mode due to reduction of the distinct physicochemical properties between acidic and basic neurochemicals. The MS/MS spectra of neurochemicals exhibited specific ions, such as losses of amine, methanol, or methyl formate molecules from protonated molecules, enabling selection of appropriate multiple reaction monitoring (MRM) ions for selective and sensitive detection. The developed method was validated in terms of linearity, limit of detection (LOD) and limit of quantification (LOQ), precision, accuracy, and recovery. The correlation coefficients (R-2) of calibration curves were above 0.9961. The ranges of LODs and LOQs were 0.1-3.6 ng/mL and 0.3-12.0 ng/mL, respectively. The overall precision and accuracy were 0.52-16.74% and 82.26-118.17%, respectively. The method was successfully applied to simultaneously profile the metabolic pathways of tyrosine, tryptophan, and glutamate in Parkinson's disease patient urine (PD, n = 21) and control urine (n = 10). Significant differences (P <= 0.01) between two groups in the activity of phenylethanolamine N-methyltransferase (PNMT) and alcohol dehydrogenase (ADH) were observed. In conclusion, this method provides reliable quantification of a wide range of neurochemicals in human urine and would be helpful for finding biomarkers related to specific neuronal diseases. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: BENZOYL CHLORIDE DERIVATIZATION; BIOLOGICAL SAMPLES; NEUROTRANSMITTER DISORDERS; PARKINSONS-DISEASE; ALZHEIMERS-DISEASE; ACIDIC METABOLITES; CATECHOLAMINES; METABOLOMICS; MICROEXTRACTION; QUANTIFICATION